2010
DOI: 10.1039/c0dt00431f
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the intramolecular acetate-mediated formation of ruthenium vinylidene complexes: a ligand-assisted proton shuttle (LAPS) mechanism

Abstract: The ruthenium bis-acetate complex Ru(κ(2)-OAc)(2)(PPh(3))(2) reacts with HC≡CPh to afford the vinylidene-containing species Ru(κ(1)-OAc)(κ(2)-OAc)(=C=CHPh)(PPh(3))(2). An experimental study has demonstrated that this reaction occurs under very mild conditions, with significant conversion being observed at 255 K. At lower temperatures, evidence for a transient metallo-enol ester species Ru(κ(1)-OAc)(OC{Me}O-C=CHPh)(PPh(3))(2) was obtained. A comprehensive theoretical study to probe the nature of the alkyne/viny… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 54 publications
2
44
0
Order By: Relevance
“…Such a concerted H 2 -formation process with the assistance of a HCOOH molecule is remarkably different from the step-by-step one shown in Figure 1. Similar examples of ligand-assisted proton migrations in the area of organometallic chemistry, have been reported in several recent publications, 40,[44][45][46] including the so called CMD mechanism by Fagnou et al, 40 AMLA mechanism by…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…Such a concerted H 2 -formation process with the assistance of a HCOOH molecule is remarkably different from the step-by-step one shown in Figure 1. Similar examples of ligand-assisted proton migrations in the area of organometallic chemistry, have been reported in several recent publications, 40,[44][45][46] including the so called CMD mechanism by Fagnou et al, 40 AMLA mechanism by…”
Section: Resultsmentioning
confidence: 78%
“…Macgregor and Davies, 44 LAPS mechanism by Lynam and Slattery, 45 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 without the involvement of the γ-NH functionality and also to the situation where the γ-NH functionality is substituted by an O atom. Figure 3 shows the calculated results for the rate determining state along the pathway where the γ-NH functionality acts as a spectator, when the HCOOH protonates the hydride to form H 2 .…”
Section: Resultsmentioning
confidence: 99%
“…A 31 P{ 1 H} NMR spectrum of the reaction mixture exhibited two very broad resonances in the region d 66, at a chemical shift similar to that observed for pure 1a and for cis-[Ru (k 2 -O 2 CPh) 2 (PPh 3 ) 2 ], 1b (q.v.). Related complexes possessing mutually trans-phosphine ligand typically exhibit resonances in the 31 P{ 1 H} spectrum between d 40 and 30 [16,17]. We therefore concluded that rapid exchange of acetate and benzoate ligands was occurring, even at room temperature.…”
Section: Stoichiometric Studiesmentioning
confidence: 90%
“…These products are thought to arise via intramolecular attack of a coordinated carboxylate ligand onto the a-carbon of a vinylidene ligand (Scheme 6b) [22,42]. In related studies, we have demonstrated that the acetate ligand in complexes of type 3 may undergo facile nucleophilic attack at the a-carbon of the vinylidene ligand to give isolable metallo-enol esters 11 (Scheme 6c) [17]. Indeed, in stoichiometric studies we have shown that protonation of 11 with acetic acid affords 7a and 10a [43].…”
Section: Mechanistic Considerationsmentioning
confidence: 94%
See 1 more Smart Citation